Molecular Characterization of Bovine Deltapapillomavirus in Equine Sarcoids in Egypt - Nader Maher Sobhy; Walid Refaai; Rahul Kumar; Christiana Rezk Bottros Youssef; Sagar Mal Goyal (Veterinary Medicine International)
Bovine papillomaviruses (BPVs) commonly cause sarcoids in equines worldwide. Equine sarcoids (ESs) reduce the working ability of draft animals and produce untoward cosmetic changes in racing and dancing equine. In this study, nine horses and 16 donkeys with sarcoids were presented to Zagazig University Veterinary Clinic, Zagazig, Egypt. Of these, eight horses and six donkeys were found to be infected with BPV. On sequencing, all 14 viruses were found to be BPV1, which were distributed in two clades without specific differentiation among papillomaviruses (PVs) of donkeys, horses, and cattle. Comparison of 135 aa (319–454) of the sequenced L1 gene with reference strains revealed three conservative mutations (D346N, Q398E, and F441Y) and two nonconservative mutations (T348N and K351T). Illumina sequencing revealed that PVs of donkeys and horses were identical and had 98.5% identity with the closest reference sequence (KX907623) of BPV1. In addition, there was high identity among all genes except E5 and L2. The substitution ranged between 0.5% (nt) and 0.89% (aa) in E4 and 5.18% (nt) and 6.81% (aa) in E5. These results indicate that BPV1 is the main cause of ESs in Egypt without marked phylogenetic variation among PVs of cattle, horses, and donkeys.